Historiográfia a szintézisíráshoz 3.: A magyar tragédiák kora 1944. március 19–1948. június 12 - Gulyás, László (Közép-Európai Közlemények, 2024)
The important task of national-conservative-civilian historiography nowadays is to create of synthesis of the history of the „short Hungarian 20th century. The presen study is one of the three steps in this work. It reviews Hungarian language literature dealing with the age of hungarian tragedies 19. March 1944 – 12. June 1948.